2020
DOI: 10.1027/1864-9335/a000402
|View full text |Cite
|
Sign up to set email alerts
|

I Saw That

Abstract: Abstract. The shooter bias effect reveals that individuals are quicker to “shoot” armed Black (vs. White) men and slower to “not shoot” unarmed Black (vs. White) men in a computer task. In three studies ( N = 386), we examined whether being observed would reduce this effect because of social desirability concerns. Participants completed a “shooting” task with or without a camera/live observer supposedly recording behavior. Cameras were strapped to participants’ heads (Studies 1a/1b) and pointed at them (Study … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 23 publications
1
0
0
Order By: Relevance
“…Past research has demonstrated that this priming procedure can by itself induce effects similar to the effects of actual social presence (e.g., Uziel, 2016;Uziel et al, 2020). In that, the present findings hold the potential to further expand the research paradigm on social presence, which has documented "social presence effects" (as described in the social facilitation literature; Bond & Titus, 1983) even in the absence of actual physical presence of others (examples include video cameras, virtual presence, prospective presence, and even implicit presence; e.g., Erber, Wegner, & Therriault, 1996;Jun et al, 2017;Kramer et al, 2020;Steinmetz et al, 2016). Future research could address the issue of whether the convergence of effects between these different manipulations stems from an activation of internalized working models relating to these basic social conditions (alone/"with others").…”
Section: Discussionsupporting
confidence: 65%
“…Past research has demonstrated that this priming procedure can by itself induce effects similar to the effects of actual social presence (e.g., Uziel, 2016;Uziel et al, 2020). In that, the present findings hold the potential to further expand the research paradigm on social presence, which has documented "social presence effects" (as described in the social facilitation literature; Bond & Titus, 1983) even in the absence of actual physical presence of others (examples include video cameras, virtual presence, prospective presence, and even implicit presence; e.g., Erber, Wegner, & Therriault, 1996;Jun et al, 2017;Kramer et al, 2020;Steinmetz et al, 2016). Future research could address the issue of whether the convergence of effects between these different manipulations stems from an activation of internalized working models relating to these basic social conditions (alone/"with others").…”
Section: Discussionsupporting
confidence: 65%